Representasi Ekologis dalam Tradisi Tawar Penggel (Pengobatan Patah Tulang) Etnik Batak Karo: Suatu Kajian Ekolinguistik - Tarigan, Sarah Nathasia; Herlina, Herlina; Tampubolon, Flansius; Sinulingga, Jekmen; Purba, Asriaty R (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2025)
This study examines the practice of Tawar Penggel as a traditional healing system of the Batak Karo community in North Sumatra, in the form of a herbal oil remedy (minak) made from 28 local plant species used to treat bone fractures and musculoskeletal disorders. The research employs a descriptive qualitative method through participatory observation, in-depth interviews, and field documentation conducted in Suka Julu Village, Karo Regency. The findings indicate that the practice of Tawar Penggel is still actively preserved by the Batak Karo community in Suka Julu Village, Berastagi District, Karo Regency. The practice involves 28 local plant species as the main ingredients in the preparation of minak, including leaves, roots, stems, tubers, sap, and spices. All materials are sourced from the surrounding environment, both from wild-growing plants and those cultivated in a simple manner by the community. This study contributes to the documentation of local wisdom and the development of ecolinguistic studies grounded in tradition and environmental context.